2008
DOI: 10.1016/j.addbeh.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A double blind, placebo-controlled trial that combines disulfiram and naltrexone for treating co-occurring cocaine and alcohol dependence

Abstract: BACKGROUND-This is a double blind, placebo-controlled trial that evaluated the efficacy of disulfiram, naltrexone and their combination in patients with co-occurring cocaine and alcohol dependence.METHODS-208 patients were randomized to disulfiram (250mg/day), naltrexone (100mg/day), the combination, or placebo for 11 weeks. Outcomes were in-trial abstinence from cocaine and/or alcohol.RESULTS-Few safety concerns were reported, although medication adherence was low in a number of patients for both medications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 63 publications
1
64
1
8
Order By: Relevance
“…None found any significant benefit for active medication (50mg/d [68,69], 100mg/d [54,55] 150mg/d [56]) in terms of outcomes for cocaine use, comorbid with alcohol, although this may have been masked by gender differences [56]. Pettinati et al [56] investigated the effect of naltrexone 150mg vs placebo as a relapse prevention agent, and found that at higher dose there was significantly greater reporting of nausea in the naltrexone group (53.7% vs. 26.8%, , p < 0.05), and in women more than men on the active medication (52.1% vs. 35.3%, , p < 0.05).…”
Section: Cocaine and Alcohol Dependence (Cad)mentioning
confidence: 99%
See 4 more Smart Citations
“…None found any significant benefit for active medication (50mg/d [68,69], 100mg/d [54,55] 150mg/d [56]) in terms of outcomes for cocaine use, comorbid with alcohol, although this may have been masked by gender differences [56]. Pettinati et al [56] investigated the effect of naltrexone 150mg vs placebo as a relapse prevention agent, and found that at higher dose there was significantly greater reporting of nausea in the naltrexone group (53.7% vs. 26.8%, , p < 0.05), and in women more than men on the active medication (52.1% vs. 35.3%, , p < 0.05).…”
Section: Cocaine and Alcohol Dependence (Cad)mentioning
confidence: 99%
“…Five RCTs have investigated the safety and efficacy of naltrexone in the treatment of comorbid alcohol and cocaine dependence (CAD) in relapse prevention [54,56,68] or abstinence initiation [55,69]. None found any significant benefit for active medication (50mg/d [68,69], 100mg/d [54,55] 150mg/d [56]) in terms of outcomes for cocaine use, comorbid with alcohol, although this may have been masked by gender differences [56].…”
Section: Cocaine and Alcohol Dependence (Cad)mentioning
confidence: 99%
See 3 more Smart Citations